Application of 1-D and 2-D Discrete Wavelet Transform to Crack Identification in Statically and Dynamically Loaded Plates - KNITTER-PIĄTKOWSKA, Anna; GUMINIAK, Michał Jan (Engineering Transactions, 2020)
The paper presents the problem of damage detection in thin plates while considering the influence of static and dynamic characteristics, especially with regard to the modes of vibration as well as the excitation by static loads. The problem of Kirchhoff plate bending is described and solved by the Boundary Element Method (BEM). Rectangular plates supported on boundary or plates supported on boundary and resting on the internal columns are examined. A defect is introduced by the additional edges forming a crack in the plate domain. The analyses of static and dynamic structural responses are carried out with the use of Discrete Wavelet Transform (DWT). Signal decomposition according to the Mallat pyramid algorithm is applied. To obtain a more adequate input function subjected to DWT the white noise disturbing the signal is considered together with the structural response. In the dynamic experiments the plate undergoes vibrations similar to natural modes. The measured variables are static deflections and vertical displacement amplitudes. All of them are established at internal collocation points distributed alongside the line parallel to selected plate edge.